Mind, value, and cosmos on the relational nature of ultimacy - Davis, Andrew M. 1987- (Lexington Books, 2020)
"A engaging dialogue with the modern "axionoetic" proposals of A.N. Whitehead, Keith Ward, and John Leslie, arguing for the relational nature of ultimacy wherein Mind and Value, Possibility and Actuality, God and the World are affirmed as ultimate only in virtue of their relationality. This relationship Whitehead calls "mutual immanence.""--
Keywords: Whitehead, Alfred North -- 1861-1947; Ward, Keith -- 1938-; Metaphysik; Endlichkeit; Relation; Whitehead, Alfred North / 1861-1947; Relationism; Metaphysics